PEMAHAMAN TREN SAAT INI SEBAGAI LANGKAH AWAL PENGUATAN NILAI-NILAI PANCASILA - Kartoli Kartoli; Helda Risman (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. It is inevitable that Pancasila has become a unifier and guide to the life of the nation and state. In line with the dynamics of the era, of course, in its application needs continuous efforts in its adjustment and strengthening. For this reason, understanding the current situation and conditions is important to be a concern. This paper tries to explain the tendency of the current situation and conditions in the context of evaporation of the Pancasila values. The related literature study was used by the autor to compile the main idea points referring to the current situation and conditions and the need for a relevant mindset to contemporary times without losing the essence of strengthening the values of Pancasila. It was hoped that this paper may be a contribution of thought for stakeholders in relation to efforts to strengthen Pancasila as a unifying philosophy and life guide for elements of the Republic of Indonesia. Abstrak. Sudah tidak dapat dipungkiri bahwa Pancasila telah menjadi pemersatu dan panduan kehidupan berbangsa dan bernegara. Sejalan dengan dinamika perkembangan jaman, tentu dalam penerapannya perlu upaya berkelanjutan dalam penyesuaian dan penguatannya. Untuk itu, pemahaman terhadap situasi dan kondisi berjalan penting untuk menjadi perhatian. Tulisan ini mencoba memaparkan kecenderungan situasi dan kondisi saat ini dalam konteks penguapan nilai-nilai Pancasila. Kajian pustaka terkait digunakan penulis untuk merangkai pokok-pokok pikiran merujuk kepada trend situasi dan kondisi berjalan dan perlunya pola pikir yang relevan dengan masa kontemporer tanpa menghilangkan esensi penguatan nilai-nilai Pancasila. Harapannya adalah tulisan ini dapat menjadi sumbangsih pemikiran bagi pihak terkait dalam kaitannya dengan upaya penguatan Pancasila sebagai falsafah pemersatu dan pedoman kehidupan elemen dari NKRI.